1996
DOI: 10.1172/jci118565
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transforming growth factor beta receptor levels on microvascular endothelial cells during in vitro angiogenesis.

Abstract: Microvascular endothelial cells (RFCs) cultured in twodimensional (2D) cultures proliferate rapidly and exhibit an undifferentiated phenotype. Addition of transforming growth factor ␤ 1 (TGF ␤ 1) increases fibronectin expression and inhibits proliferation. RFCs cultured in three-dimensional (3D) type I collagen gels proliferate slowly and are refractory to the anti-proliferative effects of TGF ␤ 1. TGF ␤ 1 promotes tube formation in 3D cultures. TGF ␤ 1 increases fibronectin expression and urokinase plasminoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(88 citation statements)
references
References 68 publications
4
83
0
1
Order By: Relevance
“…Our data are in agreement with previous results obtained with TGFβ in collagen type I capillary morphogenesis of rat epididimal fat pad endothelial cells [27], and with those reported in fibrin gels for bovine aortic endothelial cells [28]. The similarity of results we have obtained with Matrigel matrix and Matrigel matrix GFR simplifies the interpretation of the data.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in agreement with previous results obtained with TGFβ in collagen type I capillary morphogenesis of rat epididimal fat pad endothelial cells [27], and with those reported in fibrin gels for bovine aortic endothelial cells [28]. The similarity of results we have obtained with Matrigel matrix and Matrigel matrix GFR simplifies the interpretation of the data.…”
Section: Discussionsupporting
confidence: 92%
“…This type of difference between 2-and 3-dimensional models has already been described for transforming growth factor-␤1. 32 Among the mechanisms involved in OSM-induced endothelial cell proliferation, we observed that OSM stimulated the secretion of VEGF on HMEC-1s, a factor known to induce proliferation of endothelial cells. However, because LIF, which induces a proliferative effect, did not induce secretion of VEGF, we can assume that the proliferative effect of OSM is not totally due to the secretion of VEGF.…”
Section: Vasse Et Almentioning
confidence: 85%
“…Although our data are most consistent with a heterotetrameric (T␤RI) 2 (T␤RII) 2 receptor complex, and we have obtained similar results with several cell lines, there are suggestions in the literature that the stoichiometry of the complex may vary. For example, the ratio of T␤RI to T␤RII in microvascular endothelial cells was significantly higher in three-dimensional versus two-dimensional cultures, corresponding to increasing resistance to the anti-proliferative but not the matrix-inducing effects of TGF-␤ (35). In other cell types, including bone, the ratio of type I to type II receptors may also be important, particularly in differentiating growth inhibition from other effects of TGF-␤ (36 -38).…”
Section: Discussionmentioning
confidence: 99%